Factors Associated with Quality of Postnatal Care in Kenya: an analysis of the 2022 Kenya demographic and health survey - (:unkn) unknown (Archives of Public Health, 2024)
Despite the significant contribution of postnatal care (PNC) to maternal and newborn survival, few studies have explored the concept of the quality of PNC received by mothers in Kenya. Therefore, this study aimed to determine the prevalence and factors associated with the quality of PNC in Kenya. Secondary data from the Kenya Demographic and Health Survey (KDHS) of 2022 were analyzed, comprising 11,863 women who were aged 15 to 49 years. The quality of PNC was indicated as receiving all components of PNC in the first two days after childbirth. Multivariable logistic regression was conducted to determine the factors associated with the quality of PNC, using SPSS, version 20. Out of the 11,863 women, 39% (95% CI: 37.0-40.9) had received all components of PNC in the first two days after childbirth. Additionally, older women aged 35–49 years (AOR 1.88, 95%CI: 1.07–3.29), those who made decisions to seek health care jointly (AOR 1.48, 95%CI: 1.18–1.85), those who owned a telephone (AOR 1.36, 95%CI: 1.05–1.76), women who received quality antenatal care (AOR 4.62, 95%CI: 3.69–5.76), older women aged 30–34 years at the time of their first childbirth (AOR 2.25, 95%CI: 1.11–4.55), those who gave birth through cesarean section birth (AOR 1.93, 95%CI: 1.49–2.49), those who gave birth at public health facilities (AOR 1.69, 95%CI: 1.01–2.82) and those who received quality intrapartum care (AOR 1.87, 95%CI: 1.43–2.43) when compared with their counterparts were more likely to receive quality PNC. On the other hand, women from other provinces of Kenya i.e., Western (AOR 0.51, 95%CI: 0.33–0.80), and Rift Valley (AOR 0.57, 95%CI: 0.39–0.81), those who gave birth to female children (AOR 0.75, 95%CI: 0.61–0.91) and those who reported to have not been respected at all times during their hospital stay (AOR 0.49, 95%CI: 0.29–0.82) when compared with their counterparts were less likely to receive quality PNC. The proportion of mothers receiving quality PNC was found to be low. The study also highlights the need to continue encouraging mothers to attend numerous ANC visits. Moreover, emphasis should be placed on providing quality ANC, intrapartum care, and respectful maternity care by health workers. Targeted interventions to increase access to quality PNC may need to focus on young mothers, mothers living in certain regions of Kenya, and those giving birth to female babies, most especially at private health facilities, and through vaginal birth.